ANALISIS SEMANTIK PADA MANTRA SUKU BUGIS DI PAGATAN KECAMATAN KUSAN HILIR - Husni Mubarak; Gonita Lopiah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2020)
The objectives of this study were (1) To determine the type of meaning (semantics) in the Bugis herbal medicine mantra. (2) To find out the types of healing spells for the Bugis tribe in Pagatan. The benefits of this research consist of theoretical benefits and practical benefits. Qualitative descriptive research method. The data in this research is in the form of a Bugis mantra in Pagatan which is obtained from interviews and literature studies. The instrument in this study was the researcher himself. The data collection technique was carried out by recording and recording the mantras that the informants said. The results of the analysis of the meaning of the Bugis mantra in Pagatan, Kusan Hilir District, that there are types of meaning (semantics) such as: lexical, grammatical, connotative, denotative, referential, non-referential. From the Bugis healing mantra in Pagatan, Kusan Hilir Subdistrict, which consists of twelve healing spells for various types of diseases such as: stomachache, headaches, vomiting, body aches, toothaches, genie disorders, eye pain and cancer as well as spells for all types disease. Keywords ; Bugis Mantra, and Semantic words.